Financialisation, regional economic development and the coronavirus crisis: a time for spatial monetary policy? - Sokol, Martin (My University, 2021)
This paper argues that ‘spatial monetary policy’ may be needed to achieve more territorially balanced economic development. Central banks have been key in fostering financialised economies while also preventing their collapse in times of crisis—a role further strengthened by the coronavirus pandemic. Central banks have thus become the most powerful economic policy-making institutions, just when spatial disparities are likely to deepen. In the context of crisis-ridden financialised capitalism, regional development policies should consider the spatial implications of central bank interventions and recognise monetary policy as a key element of spatial policy. Simultaneously, monetary policy should embrace an explicit spatial agenda.
PUBLISHED
https://doi.org/10.1093/cjres/rsab033
Keywords: Financialisation; Crisis; Central banks; Monetary policy; Spatial policy; Regional development; Inclusive Society; Smart & Sustainable Planet; financial geography